Comparative study of heuristic algorithm ABC and GA considering VPI for network reconfiguration - Sulaima, Mohamad Fani; Mohamad, Mohd Fadhlan; Jali, Mohd Hafiz; Wan Daud, Wan Mohd Bukhari; Baharom, Mohamad Faizal (2014)
Distribution Network Reconfiguration (DNR) is an important part of power distribution automotive system. In order to improve the system security as well as minimize the power losses in the system; it can be done by considering a DNR with the superlative optimization method. This paper presents the comparison study of two heuristic methods which are Artificial Bee Colony (ABC) and Genetic Algorithm (GA). Their performance and impact in terms of Voltage Profile Improvement (VPI) and power loss in the network system are investigated. The effectiveness of both methods will be tested in an IEEE 33-bus system. The analysis of the results is hope to help the researchers in improving the voltage profile and expands the system security in the future.